4+3p-1=8p+7-3p

Simple and best practice solution for 4+3p-1=8p+7-3p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+3p-1=8p+7-3p equation:


Simplifying
4 + 3p + -1 = 8p + 7 + -3p

Reorder the terms:
4 + -1 + 3p = 8p + 7 + -3p

Combine like terms: 4 + -1 = 3
3 + 3p = 8p + 7 + -3p

Reorder the terms:
3 + 3p = 7 + 8p + -3p

Combine like terms: 8p + -3p = 5p
3 + 3p = 7 + 5p

Solving
3 + 3p = 7 + 5p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-5p' to each side of the equation.
3 + 3p + -5p = 7 + 5p + -5p

Combine like terms: 3p + -5p = -2p
3 + -2p = 7 + 5p + -5p

Combine like terms: 5p + -5p = 0
3 + -2p = 7 + 0
3 + -2p = 7

Add '-3' to each side of the equation.
3 + -3 + -2p = 7 + -3

Combine like terms: 3 + -3 = 0
0 + -2p = 7 + -3
-2p = 7 + -3

Combine like terms: 7 + -3 = 4
-2p = 4

Divide each side by '-2'.
p = -2

Simplifying
p = -2

See similar equations:

| 1/2d+3=2 | | 6x+12y=77 | | -1.5x+-14.5=-31 | | -2(y-4)=20+2y-12 | | 24.6=29+a(14.51) | | (7/2+2*2)*10= | | 0.7n=-3.5 | | -8(n-5)=2(4n+11) | | 2000+0.05=3600 | | 7x+9+4(x+4)+2= | | 14(t+9)=84 | | -3x-17=-8 | | (x-110)+(3x-10)+(2x)=180 | | 8(7+6b)= | | 2x-125=400 | | 26-2x=2x+3 | | 4(y+7)=5(y-8) | | 46.5=5.25+15 | | 14ab=c | | -89-17= | | (110-x)+(3x-10)+(2x)=180 | | -9x+4=-6+-17 | | 45y^2+10y=0 | | -3-3(1-7x)=4x-40 | | ln(7x)=ln(40-x) | | -5(5W+1)=25 | | w-(-7)=51 | | 80-4x=100-y | | 10+24n=130 | | 6+3z-3=7z+12-3z | | x-(3x+4)=10 | | -3.4x+2=-3.72 |

Equations solver categories